Briquetting of Dry Sugarcane Leaves by Using Press Mud, Cow Dung, and Buffalo Dung as Binders - Patil, R.A. (Hindawi Limited, 2021)
The world's population is increasing rapidly. This means that energy consumption and demand for energy are also increasing at the same rate. It is estimated that energy will need to be provided to 9 to 10 billion people by 2040. India is a leading consumer of energy in the world. In particular, it consumes a large amount of oil and natural gas to fulfil its energy demand. Due to uncertainty in the supply of oil and natural gas and their prices as well as environmental pollution, there is a need to shift towards other energy sources. Biomass is one of the first energy sources with specific properties and abundant availability. Today, 10 to 14 of the world's energy supply is provided by biomass sources. Using agricultural waste (biomass) to make briquettes to generate power can be an alternative solution to the problems related to their disposal and pollution. The present work investigates the optimum ratio of dry sugarcane leaves to binders and optimum load and selects the best binder (cow dung, buffalo dung, and press mud) for making high-quality briquettes. The physical parameters and proximate analysis of the dry sugarcane leaf briquettes with the cow dung, buffalo dung, and press mud binders are investigated. The dry sugarcane leaf briquettes with the cow dung binder have the highest gross calorific value, net calorific value, split tensile strength, tumbling resistance, shatter resistance, and energy density ratio (16262.31 kJ/kg, 15362.1 kJ/kg, 7.164 kN/m2, 87.84, 12.75, and 0.9296, respectively). The estimated results show that cow dung is a better binder for making high-quality dry sugarcane leaf briquettes than the buffalo dung and press mud binders. Â© 2021 Rahul A. Patil et al.